(untitled) (Journal of the College of Basic Education, 2022)
The Cockroaches is historically Known from insects and old . Species of which are currently scattered resemble fossilized assets . Description of 4000-5000 were Somewhat divided in to the 440 genera of Cockroaches Ismail ( 1) feeding on different kinds of food which made them a varirty of nutrition depending on the members of her mouth biting chewing . Given the lack of studies on this Cockroache and there is no proof its importance in medical transfer bacteria in Iraq . It has been prepared in this research . Through living in nearby places for humans to be a Candidate as a vector a mechanic bacteria . Rueger& Olson (2) . Have many kinds of bacteria by isolation Glasere (3) . Steinhaus (4) . Said Rivault et.al. (5). The possibility of a Kind bacteria isolated from the total 157 model for Cokrouches in different environment and 56 were 14 of them Causing disease in humans .